Outcomes and cost minimisation associated with outpatient parenteral antimicrobial therapy (OPAT) for foot infections in people with diabetes. Issue 6 (19th May 2015) - Malone, Matthew; West, Dana; Xuan, Wei; Lau, Namson S.; Maley, Michael; Dickson, Hugh G.
Abstract Objective To determine clinical outcomes in patients with diabetic foot infections receiving outpatient parenteral antimicrobial therapy (OPAT), to evaluate cost savings from the use of OPAT and to analyse demographic, clinical and laboratory data that may predict OPAT failure. Research Design and Methodology A retrospective cohort analysis was conducted between 1 January 2007 and 7 July 2012 at a tertiary referral hospital in metropolitan Sydney. Patients with diabetic foot infection were identified from the outpatient parenteral antimicrobial therapy database. Demographic, clinical, laboratory and operative report data were obtained from patient charts and electronic medical records. Potential cost savings were calculated on the estimated cost of expenditure versus the expected savings. Linear regression was used to explore outcomes associated with outpatient parenteral antimicrobial therapy failure. Results Fifty‐nine patients were identified over the 5‐year study period. The outpatient parenteral antimicrobial therapy success rate for diabetic foot infections was 88%. Following the resolution of the primary episode of infection, new infective episodes within the study period were high (n = 26, 44%). Regression analysis of variables for OPAT failure failed to indicate any factors reaching statistical significance. A total of 1569 days were saved by using outpatient parenteral antimicrobial therapy for an estimated total cost saving of 983 645 or 16 672 per patient. Conclusion Outpatient intravenous therapy for diabetic foot infections is an effective mode of treatment that can contribute to significant healthcare savings. High re‐infection rates associated with diabetes foot ulceration in this population underline the need for close monitoring and management of these patients in multidisciplinary high‐risk foot setting. Copyright © 2015 John Wiley & Sons, Ltd.